Avaliação de sorventes para remoção de clorofila na determinação de agrotóxicos em espinafre empregando método QuEChERS e GC-ECD - Mann, Mariele da Silva Mazuim (2017)
Vegetables are classified as greens when used on green parts and play an important role in human diet and nutrition. These foods are sources of vitamins, antioxidant polyphenols, essential amino acids, fibers, minerals, and a wide range of bioactive substances. This class of food is extremely rich in pigments, such as chlorophylls and carotenoids, which are responsible for conferring its color and are used as a parameter of maturity, quality and freshness. The instinctive preference and the pursuit for a healthier life lead to a naturally colored foods diet. On the other hand, like many other crops, vegetables are susceptible to pests and other diseases, and the application of plant protection products is a common practice in agriculture to overcome this problem and increase productivity. Thus, it is necessary to monitor the products intended for human consumption, which may pose risks to human health, resulting from chronic dietary exposure. However, the abundant amounts of chlorophyll in sample matrix requires a preliminary sample preparations capable of providing clean extracts and suitable recoveries of interest analytes. The main objective of this work was to optimize a sample preparation method by using different proportions and combinations of sorbents for the removal of pigments, especially chlorophyll, present in extracts of spinach samples. The experiments were evaluated by gravimetric tests, thin layer chromatography (TLC) and qualitative analysis by high performance liquid chromatography with ultraviolet/visible detection (HPLC-UV/Vis). After the optimization, a multi-residue method was developed and validated for the determination of 33 pesticides in spinach using QuEChERS acetate method and gas chromatography with electron capture detector (GC-ECD). The cleaning of the extracts was performed by solid phase extraction (SPE) with sorbents NH2, Z-Sep+ and Na2SO4 with elution by gravity. The validation results were satisfactory with recoveries between 70 and 120% and RSDs ≤20%. The curves were prepared in the matrix extract, due to the presence of a strong matrix effect for most of the compounds. The limits of detection and quantification were from 3.0 to 7.5 and 10 to 25 μg kg-1, respectively. The proposed method proved to be adequate for the determination of multiresidues of spinach pesticides, as well as the cleaning of the extracts showed high efficiency, giving satisfactory sensitivity and detectability to the method, since all the parameters suggested for the validation of chromatographic methods are within the limits.